Servant Leadership and Affective Organizational Commitment among Malaysian Police Officers - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan (Future Academy, 2019)
The purpose of this paper is to examine the relationship between servant leadership and affective organizational commitment. The independent variable, servant leadership, is formed by agape love, empowerment, humility, altruism, visionary and trust while the dependent variable is affective organizational commitment. A total of 168 questionnaires were obtained from the police officers, working in a few Royal Malaysian Police Division, which yielded a response rate of 42%. The results revealed that five variables of the servant leadership which is agape love, empowerment, altruism, trust, and visionary are significantly related to the organizational affective organizational commitment. Theoretically, this paper contributes to the literature on servant leadership and organizational commitment. Practically, top management of Police Department of Malaysia should consider trainings and courses on leadership, value, and charisma that boost leadership and affective organisational commitment of their employees. In conclusion, this paper reveals the importance of agape love, empowerment, altruism, trust, and visionary as factors of servant leadership in affecting organizational commitment of police